Metafora Konseptual Lima Jari dalam Sastra Jawa: Analisis Semantik Kognitif (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
The existence of human fingers has an important role in moral concept based on Javanese culture. Beside as the body languages or gesture, the fingers also have an important position to expressing about moral value. There are some of Javanese literature—poem or oral tradition—that contain moral didactics “how to be a good human”. The aim of this paper is to describe about the fingers in Javanese metaphor concepts based cognitive semantics. The theoretical approach used is the opinion of Johnson and Lakoff, and several relevant previous studies. The research process includes data observation through literature review, data grouping, data reduction, and analysis. The results of this study indicate that the expressions of the fingers in Javanese society state the normative behavior or ethics that must be carried out. This can be seen in the expressions ‘pol-polan’ (thumb), ‘panuduh’ (pointing finger), ‘panunggul’ (middle finger),’ memanis’ (ring finger), and ‘thak-thik’ (little finger). Beside that, the fingers also have the meaning that everyone must balancing and make solidarity. Keywords: Javanese literature; the fingers; moral didactics; cognitive semantics.